Sugar-sweetened carbonated beverage consumption and childhood/adolescent obesity: a case–control study. Issue 10 (31st January 2014) - Martin-Calvo, Nerea; Martínez-González, Miguel-Angel; Bes-Rastrollo, Maira; Gea, Alfredo; Ochoa, Ma Carmen; Marti, Amelia; GENOI Members
Abstract Objective To assess the association between the consumption of sugar-sweetened carbonated beverages (SSCB) and obesity in children and adolescents from Navarra (Spain). Design We used a matched case–control study design. The exposure, SSCB consumption (1 serving: 200 ml), was measured with a previously validated FFQ. Anthropometrical measures were taken using standardized protocols. The outcome, obesity, was defined as BMI above the age- and sex-specific 97th percentile according to the Spanish reference charts. In the analysis we used conditional logistic regression. Potential confounders were controlled using a multivariable model. Setting Subjects were recruited in the paediatric departments of the Universidad de Navarra Clinic and the Navarra Hospital Complex, and in three primary health centres of Navarra. Controls were recruited when attending for a routine medical examination or vaccination. Subjects One hundred and seventy-four obese children and 174 individually sex- and age-matched controls, 52·87 % boys, with a mean age of 11·6 years. Exclusion criteria were dietary interventions, exposure to hormone treatment, development of secondary obesity due to endocrinopathy and serious intercurrent illness. Results Independently of other factors, high consumption of SSCB (>4 servings/week) was significantly associated with obesity (OR = 3·46; 95 % CI 1·24, 9·62; P = 0·01). Besides, each additional daily serving of SSCB was associated with a 69 % relative increase in the risk of obesity (OR = 1·69; 95 % CI 1·04, 2·73; P = 0·03). Conclusions We found a strong and significant association between SSCB consumption and obesity risk. Our results suggest a monotonic dose–response linear shape for this association in children and adolescents (P for trend = 0·02).